2005
DOI: 10.1121/1.1921549
|View full text |Cite
|
Sign up to set email alerts
|

Sound transmission across duct constrictions with and without tapered sections

Abstract: The sound power transmission loss across duct constrictions with linearly tapered sections is studied with the finite element method. Results show that the acoustic energy distributions of transmitted waves at high frequency depend critically on the exit configuration of the constriction. The corresponding strengths of these waves are very much affected by the entrance setup of the constriction. The difference between inlet and outlet impedance of a constriction leads to weaker resonant sound transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Suitable numerical methods include the standard finite element method (FEM) and the boundary element method (BEM). For example, Tang and Lau 8 , and later Lau and Tang 9 , used the standard FEM to study tapered and convergent-divergent sections in rectangular ducts, although both studies required a large number of degrees of freedom in order to obtain a converged solution. Jeong et al 10 reviewed the application of the BEM in rectangular ductwork and demonstrated that by discretising the duct into multiple domains one may generate an efficient BEM algorithm that may be applied to larger ductwork.…”
Section: Introductionmentioning
confidence: 99%
“…Suitable numerical methods include the standard finite element method (FEM) and the boundary element method (BEM). For example, Tang and Lau 8 , and later Lau and Tang 9 , used the standard FEM to study tapered and convergent-divergent sections in rectangular ducts, although both studies required a large number of degrees of freedom in order to obtain a converged solution. Jeong et al 10 reviewed the application of the BEM in rectangular ductwork and demonstrated that by discretising the duct into multiple domains one may generate an efficient BEM algorithm that may be applied to larger ductwork.…”
Section: Introductionmentioning
confidence: 99%
“…17 The finite-element method can cater for any non-planar air motions at the mouths of the sidebranch tubes and thus should be more accurate than the simplified theory in Sec. II.…”
Section: The Computational Modelmentioning
confidence: 99%